Business-Making Supported Via the Application of Big Data: Insights from a Literature Review - Rusgowanto, Fransisca Hanita (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The application of big data has revolutionized the way businesses make decisions and strategize in an ever-evolving digital landscape. This study highlights the transformative role of big data in supporting business decision-making processes, particularly through its ability to generate actionable insights, optimize operational efficiency, and enhance customer satisfaction. Key applications discussed include market trend analysis, predictive analytics, and personalized marketing, which demonstrate how big data enables businesses to adapt to complex market dynamics. Despite its significant potential, this study also identifies challenges such as data security, privacy issues, and the shortage of skilled professionals in data analytics. Based on a comprehensive literature review, the findings emphasize the critical contribution of big data in fostering innovation, improving productivity, and supporting sustainable business practices. By adopting strategic frameworks for big data integration, organizations can enhance their competitive advantage and achieve long-term growth. This study also underscores the importance of collaboration between technology providers and businesses to maximize the potential of big data and provides practical recommendations for its successful implementation.